Infection with hepatitis C virus in porphyria cutanea tarda. - Lima, J; Serejo, F; Gloria, H; Ramalho, F; Moura, M C (Acta Médica Portuguesa, 1996)
The authors make a literature review on hepatitis C virus infection in porphyria cutanea tarda, illustrated by one clinical case. They also present some considerations about pathophysiologic mechanisms involved in this association.